UPAYA MENGATASI HAMBATAN DALAM PENANAMAN NILAI KARAKTER PADA SISWA PENDIDIKAN DASAR MUHAMMADIYAH - Ratnasari Diah Utami (Universitas Muhammadiyah Semarang, 2015)
The general objective of this research is to disclose proposed solution which can be implemented by teachers in SD Muhammadiyah Baturan Karanganyar to overcome obstacles in instilling character. This research is descriptive qualitative study. The sources of the research data consists of the informant, places (events), and document. Data collection technique used in this study were (1) observations (2) in-depth interviews with principals, teachers, and students of SD Muhammadiyah. (3) Documentation, and (4) FGD. To test the validity of the data used triangulation of data and informants. Analysis using the interactive analysis techniques that includes four components: data collection, data reduction, data display, and conclusion. The results of this research is: The solutions offered can be implemented by teachers in SD Muhammadiyah Baturan to overcome obstacles in instilling character in students is through giving strict rules, designing learning strategies, routine in instilling a good attitude, hold the fabric of the relationship with the parents, as well as giving / be a good role model to the students.Keywords: character, education, solution